A Wandering View: Writing Jews and Jewishness on British Television. - Jordan, James (European Judaism, 2014)
This article discusses four different representations of Jews and Jewishness as seen on British television since 1960. The first three - Victor Gollancz's appearance on Face to Face (1960), an episode of the situation comedy Please Sir! (1968), and Simon Schama's The Story of the Jews (2013) all feature individuals who consciously articulate their identity as 'a Jew' in different ways. The final section argues for the subconscious presence of Jewishness in the central character of the BBC's long-running series Doctor Who.